OP0029 Baricitinib, An Oral Janus Kinase (JAK)1/JAK2 Inhibitor, in Patients with Active Rheumatoid Arthritis (RA) and an Inadequate Response to TNF Inhibitors: Results of the Phase 3 RA-Beacon Study. (9th June 2015) - Genovese, M.C.; Kremer, J.; Zamani, O.; Ludivico, C.; Krogulec, M.; Xie, L.; Beattie, S.; Koch, A.E.; Cardillo, T.; Rooney, T.; Macias, W.; Schlichting, D.; et al.
Abstract : Background: In ph 2 studies, baricitinib (bari) improved disease activity with an acceptable safety profile in patients (pts) with active RA naïve to biologic DMARDs (bDMARDs). 1, 2 Objectives: To report results from a ph 3 study of bari in pts with active RA and an inadequate response or intolerance to ≥1 TNF inhibitor (TNFi). Methods: Pts with active RA (TJC & SJC ≥6, hsCRP ≥3mg/L) on conventional DMARDs (cDMARDs) were randomized 1:1:1 to placebo (PBO) or bari (2 or 4 mg) QD for 24 wks. All bDMARDs were discontinued ≥28d prior to treatment. Primary endpoint was ACR20 response at Wk 12 for bari 4 mg vs. PBO. Results: Of 527 randomized pts, 57% had received ≥2 bDMARDs and 38% had received ≥1 non-TNFi bDMARD. Fewer pts discontinued treatment prior to Wk 24 on bari 2 or 4 mg vs. PBO (10%, 11%, 18%, respectively). ACR20 response at Wk 12 was higher with bari 4 mg vs. PBO (55% vs. 27%, p≤0.001). Improvements in ACR20, ACR50, ACR70, DAS28, CDAI, SDAI, and HAQ-DI were seen (Table ), many as early as Wk 1. Treatment benefit was sustained through Wk 24 for the 4 mg dose. More TEAEs occurred in pts receiving bari 2 or 4 mg compared to PBO (71%, 77%, 64%, respectively) including infections (44%, 40%, 31%, respectively). SAE rates through 24 wks were similar among pts receiving bari 2 or 4 mg or PBO (4%, 10%, and 7%, respectively) including serious infections (2%, 3%, and 3%, respectively). There were no opportunistic infections, TB, or GI perforations. Two non-melanoma skin cancers and 2 major adverse cardiovascular events, including 1 death (stroke), were seen with bari 4 mg. Lab findings were consistent with ph 2 studies. Abnormalities leading to discontinuation were infrequent. Conclusions: In pts with active RA on cDMARDs and an inadequate response to bDMARDs, once daily oral bari was associated with rapid and sustained clinical improvements through 24 wks, with an acceptable safety and tolerability profile. The largest benefit was seen with the 4 mg dose. Additional ph 3 studies in bDMARD-naive pts are ongoing. References: Keystone et al. Ann Rheum Dis 2015;24:333-340 Tanaka et al. Arthritis Rheum 2013;65(S10):S765 Disclosure of Interest: M. Genovese Grant/research support from: Abbvie, Astellas, Eli Lilly & Company, Galapagos, Pfizer, Vertex, Consultant for: Abbvie, Astellas, Eli Lilly & Company, Galapagos, Pfizer, Vertex, J. Kremer Grant/research support from: Abbvie, Amgen, BMS, Genentech, Eli Lilly & Company, Pfizer, UCB, Consultant for: Eli Lilly & Company, Employee of: Corrona, O. Zamani Grant/research support from: Eli Lilly & Company, C. Ludivico Grant/research support from: Eli Lilly & Company, M. Krogulec Grant/research support from: Eli Lilly & Company, L. Xie Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, S. Beattie Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, A. Koch Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, T. Cardillo Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, T. Rooney Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, W. Macias Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, D. Schlichting Shareholder of: Eli Lilly & Company, Employee of: Eli Lilly & Company, J. Smolen Grant/research support from: Abbvie, Janssen, MSD, Pfizer, Roche, UCB, Consultant for: Abbvie, Amgen, Astra-Zeneca, Astro, Celgene, Glaxo, Janssen, Eli Lilly & Company, Medimmune, MSD, Novartis-Sandoz, Pfizer, Roche, Samsung, Sanofi, UCB